Pelatihan Microsoft Office Untuk Kelas XII SMAN 22 Kabupaten Tangerang - Elfi Fauziah; Muhammad Rosdiana; Riswal Hanafi Siregar (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Microsoft Office is an application that is widely used both in school and in the world of work, this application consists of many applications in it and the most popular are Microsoft Word, Microsoft Excel and Microsoft Powerpoint. These three applications are important because every school or work activity or assignment cannot be separated from this program or application, especially in making reports in the form of correspondence, tables or mathematical calculations and making presentations. The problem that occurs at SMA Negeri 22 Kabupaten Tangerang is that many class XII students who want to end their schooling are still many who cannot operate Microsoft Office because high school does not have Computer, even though these three applications are very important and will often be used when they work or continue studying. Therefore, Pamulang University Lecturers carry out PKM activities in this place, the goal is that class XII students of SMA Negeri 22 Kabupaten Tangerang have basic knowledge of Microsoft Word, Microsoft Excel and Microsoft Powerpoint as well as skills in operating these three applications. With this training, it is hoped that class XII students at SMA Negeri 22 Kabupaten Tangerang will have provisions after graduation and be able to compete in the world of work in the future or these skills can be used to do college assignments for those who continue their studies. Basic material about Microsoft Office, both Microsoft Word, Microsoft Excel and Microsoft Powerpoint, such as making correspondence automatically, making good and correct reports, making tables, using cell formats, mathematical calculations as well as advanced material such as the IF function, Hlookup, Vlookup are taught in this way. regular or automated systems as well as how to make interesting presentations are also taught. So that students and students have the option to work on various kinds of problems that exist quickly and carefully.